The government's civil liability for economic insecurity; a jurisprudential analysis - حق پناه حق پناه (پژوهش‌های فقهی مسائل مستحدثه)
One of the important economic principles is justice and security. The devaluation of the national currency, severe inflation, and unusual fluctuations in the market cause economic insecurity and pressure on the weaker sections of society. Now, in response to the question of what is the civil responsibility of the government towards these economic insecurities? Considering the necessity of economic security in financial and commercial relations, reducing investment risks, ensuring the return of profits, and the effects it has on people's daily lives, the government is responsible for protecting the economic interests of the people, in charge of the general treasury, budgets, credits, and capital of the nation and the country, and all economic highways and major decisions are made with the government's perspective. Therefore, any action or behavior, whether an act or omission by the government, that leads to damage to individuals in society, whether natural or legal, must be compensated for based on the principle of loss. Given that the criterion for liability in the rule of loss is encroachment on another's property, and this issue is also compensated by receiving its equivalent, in the event that the property that was lost is an equivalent, in the first instance, the equivalent must be paid to the injured party, and in the event that there is no equivalent, the price and value of the day of the loss must be paid to the injured party. In the narrations related to the rule of loss, titles such as coexistence, attribution, conditions, etc. are not included, and therefore, in any case where loss occurs to property, whether by action or omission, by the government or a natural person, intentionally or unintentionally, it will not make a difference in the liability of the damaged party.